2019
DOI: 10.31219/osf.io/q6vzb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing mid-sagittal tongue contours in polar coordinates using generalised additive (mixed) models

Abstract: Statistical modelling of whole tongue contours has been mostly dominated by the use of Smoothing Splines Analysis of Variance (SSANOVA), although the quantitative analysis of UTI data remains a challenge. Recently, a variety of research disciplines witnessed an increased use of Generalised Additive Models (GAMs) and their mixed-effects counterpart. This family of models is a highly flexible solution which extends standard generalised linear mixed regressions to model non-linear effects. This paper offers a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Figure 13 shows midsagittal tongue contours from ultrasound imaging extracted from around the mid-point of the sustained tokens of each vowel (the front of the oral cavity is on the right side). In this figure, the tongue contours have been smoothed using a generalised additive model (Hastie & Tibshirani 1986, Wood 2006) with polar coordinates (Coretta 2019).…”
Section: Nasals and Approximantmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Figure 13 shows midsagittal tongue contours from ultrasound imaging extracted from around the mid-point of the sustained tokens of each vowel (the front of the oral cavity is on the right side). In this figure, the tongue contours have been smoothed using a generalised additive model (Hastie & Tibshirani 1986, Wood 2006) with polar coordinates (Coretta 2019).…”
Section: Nasals and Approximantmentioning
confidence: 99%
“…Early descriptive studies have suggested that declarative sentences have a falling intonational contour, as seen in our corpus in sentences (a) and (b), while questions have a rising one, as in sentences (c) and (d) (BoriCi 1987, Memushaj 2015. More recent work has proposed that different informational-structure constructs, such as topic, informational focus and contrastive focus associate with different tunes in Standard Albanian (Kapia & Brugos 2016, 2019Kapia, Kleber & Harrington 2020, Kapia, Harrington & Kleber forthcoming). The narrow focus pattern can be seen in the word murin in the polar question (c).…”
Section: Finalmentioning
confidence: 99%
“…Early descriptive studies have suggested that declarative sentences have a falling intonational contour, as seen in our corpus in sentences (a) and (b), while questions have a rising one, as in sentences (c) and (d)(Boriçi 1987;Memushaj 2015). More recent work has proposed that different informational structure constructs, such as topic, informational focus and contrastive focus associate with different tunes in Standard Albanian(Kapia & Brugos 2016, 2019 Kapia et al 2020, forthcoming). The narrow focus pattern can be seen in the word murin in the polar question (c).…”
mentioning
confidence: 99%